Perception of political corruption as a function of legislation - Krambia-Kapardis, Maria (My University, 2014)
Purpose - The main aim of the paper is to determine whether countries with enacted legislation on electoral accountability issues (such as conflict of interest, revolving doors, asset disclosure, lobbying, immunity, political party funding and a code of conduct for politicians) have lower corruption perception than countries that do not have legislation on those variables. Design/methodology/approach - The author utilised the corruption reports developed by the corruption country experts appointed by the EU DG Home and carried a correlation analysis between the above variables and the Corruption Perception Index (CPI) developed by Transparency International. Findings - A correlation was only found for the asset disclosure variable and CPI. Alternative factors borne out of the literature are briefly discussed and suggestions for future research are made. Research limitations/implications - Due to the small sample size (n = 26), the statistical analysis that could be carried out was limited. Practical implications - One policy implication of the negative finding obtained is that politicians are well advised to invest in measures that will enhance the electorate's trust in them. Passing anti-corruption legislation alone does not yield low corruption perception. Originality/value - This is the first study of its kind addressing corruption correlates by looking at electorate accountability.
Keywords: Corruption perception; Electorate accountability; EU; Political corruption; Trust